Follicular Cholecystitis Mimicking Xanthogranulomatous Cholecystitis and Malignancy: A Case Report - Martina Aineseder (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Chronic follicular cholecystitis (CFC) is a rare pathology characterized by prominent lymphoid follicles in the lamina propria distributed throughout the gallbladder wall. It has also been mentioned in the literature as lymphoid hyperplasia and pseudolymphoma. CFC represents less than 2% of cholecystectomies. Its etiopathology is mostly unknown. Most reports are based on histopathological findings, with little or no imaging analysis. We describe a case involving a 66-year-old man radiologically diagnosed as xanthogranulomatous cholecystitis (XGC) versus malignancy, revealing CFC with surrounding inflammatory changes in the cholecystectomy specimen.